Preliminary field survey on Mycobacterium bovis infection in cattle herds using caudal fold intradermal tuberculin test in two Northeastern States of Nigeria - Salisu Ibrahim; Bello Abubakar Usman; Danbirni Samaila; Adamu Saleh Saidu (International Journal of One Health, 2018)
Aim: A survey was conducted to determine the prevalence of bovine tuberculosis (bTB) in two states of Northeastern Nigeria, namely Bauchi and Gombe States, between February 2010 and November 2014 using caudal fold tuberculin (CFT) skin test.